2017
DOI: 10.1080/13880209.2017.1302967
|View full text |Cite
|
Sign up to set email alerts
|

Gelidiella acerosa protects against Aβ 25–35-induced toxicity and memory impairment in Swiss Albino mice: an in vivo report

Abstract: Context: Alzheimer’s disease (AD) is believed to develop due to deposition of β-amyloid (Aβ) peptide. Hence, efforts are being made to develop potent drug that target amyloid hypothesis.Objective: The present study explores the effect of the seaweed Gelidiella acerosa (Forsskål) Feldmann & Hamel (Gelidiellaceae) against Aβ 25–35 peptide in Swiss albino mice.Materials and methods: The animals were administered through intracerebroventricular (ICV) injection with the Aβ 25–35 peptide (10 μg/10 μL/ICV site) on 21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 38 publications
2
11
0
Order By: Relevance
“…Aβ is produced by amyloidogenic pathway, which is processing of amyloid precursor protein (APP) to Aβ via activation of two enzymes such as β- and γ-secretase [ 1 ]. In addition, Aβ-injected mice display several AD-like pathological symptoms such as the neuronal oxidative stress and neuronal apoptosis in the brain tissue [ 19 , 20 ]. Drugs such as donepezil used in AD patients for treatment of AD, attenuate the cognitive impairment by regulation of the cholinesterase inhibition in the brain [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aβ is produced by amyloidogenic pathway, which is processing of amyloid precursor protein (APP) to Aβ via activation of two enzymes such as β- and γ-secretase [ 1 ]. In addition, Aβ-injected mice display several AD-like pathological symptoms such as the neuronal oxidative stress and neuronal apoptosis in the brain tissue [ 19 , 20 ]. Drugs such as donepezil used in AD patients for treatment of AD, attenuate the cognitive impairment by regulation of the cholinesterase inhibition in the brain [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Passive avoidance test is based on tendency of mice to natural preference toward dark environment [ 32 ]. The Aβ 25–35 -induced AD mice more frequently enter the electric shock-consisted the dark chamber than electric shock-non-consisted light chamber by damage of passive avoidance ability, compared with normal mouse [ 20 , 33 ]. Our result showed that Aβ 25–35 -induced AD mice disrupted passive avoidance ability.…”
Section: Discussionmentioning
confidence: 99%
“…Crude extracts of some macroalgal species have shown neuroprotective potentials against some markers of Alzheimer’s disease in vivo. Syad and Devi [97] confirmed that benzene extracts of G. acerosa attenuated neurotoxicity induced by AB 25–35 in Swedish mice brain. G. acerosa improved memory function by attenuating cholinergic dysfunction via inhibition of acetylcholinesterase and butyrylcholinesterase.…”
Section: Therapeutic Role Of Some Macroalgae In the Management Of Admentioning
confidence: 93%
“…In addition, extracts from several marine algae have shown to either ameliorate memory impairment or enhance cognition in various in vivo models. For instance, Gelidiella acerosa attenuated Aβ25-35-induced cytotoxicity and memory deficits in mice [ 223 ], Sargassum swartzii improved memory functions in rats [ 224 ], Ishige foliacea [ 128 ], Undaria pinnatifida [ 225 ] ameliorated scopolamine-induced memory deficits in mice, Haematococcus pluvialis recovered Alzheimer’s disease in rats [ 226 ], and fermented Spirulina maxima prevented memory impairment in mice [ 227 ]. In addition, some marine algae have shown to attenuate ischemic injury in stroke models.…”
Section: Neuropharmacological Potentials Of Marine Algae and Theirmentioning
confidence: 99%